Analisis Pengaruh Program Pengentasan Kemiskinan dalam Upaya Menghasilkan suatu Model Pengentasan Kemiskinan yang Berkelanjutan (Studi Eksperimen pada Dusun Wonodadi Desa Sei. Bulan Kabupaten Kubu Raya Provinsi Kalimantan Barat) - Yani Riyani; Linda Suherma; Nizar - (Jurnal Aplikasi Manajemen, 2010)
This study aims to find a strategy/right model that can be used for poverty reduction by analyzing the effect of poverty alleviation programs in the form of exchange rights to land, direct cash aid, the implementation of the built hamlet on the growth of people’s income level in Wonodadi hamlet. This research is an experimental research that be carried out for 5 months. In the implementation of the experiment, the sample was divided into two groups of free groups and the control group. Once data is collected, the data were analyzed by using regression analysis and one-way anova. From the data analysis has been done can be concluded: first, poverty reduction programs in the form of exchange rights to land can increase people’s income, the second, poverty reduction program in the form of direct cash aid can not improve people’s income, third, built hamlet program implementation can improve the people’s income, fourth, there are income differences between the hamlets that are nurtured and a hamlet that is not nurtured.Keywords: exchange rights to land, direct cash aid, built hamlet.